Earthquakes: Steel Structures Performance and Design Code Developments - Marsh, James W. (Engineering Journal, 1993)
Major earthquakes occur several times each year throughout the world with heavy loss of life and property. Recent examples are the 1992 Cairo, Egypt earthquake with the loss of over 500 lives, and the Mexico earthquake of 1985 with the loss of 8,000 lives and the collapse of over 400 buildings. The United States has experienced many large earthquakes, with the most seismic activity to date being located in California, i.e., Loma Prieta, California, 1989, 7.1 Richter magnitude and Landers, California, 1992, 7.5 Richter magnitude. It is evident from past occurrences of earthquakes that the highly seismic regions of the United States have a serious earthquake problem, and the less serious regions in the central and eastern parts of the country now realize that they have an earthquake problem which is being addressed through adoption of the latest seismic design provisions into the BOCA and SBCCI building codes. Some of these newly acquired seismic provisions are taken from the Building Seismic Safety Council program on improved seismic safety. The Building Seismic Safety Council (BSSC) was established in 1979 under the auspices of the National Institute of Building Sciences (NIBS) as an entirely new type of instrument to develop and promulgate building earthquake hazard mitigation regulatory provisions that are national in scope. Its fundamental purpose is to enhance public safety by providing a national form that fosters improved seismic safety provisions for use by the building community in the planning, design and construction of buildings. To fulfill its purpose, the BSSC promotes the development of seismic safety provisions suitable for use throughout the United States. The BSSC believes that the regional and local differences in the nature and magnitude of potentially hazardous earthquake events require a flexible approach to seismic safety that allows for consideration of the relative risk, resources and capabilities of each community. The BSSC itself assumes no standards-making and promulgating role; rather, it advocates that code and standards formulation organizations consider BSSC recommendations for inclusion into their documents and standards. A recommendation that is taking place today in code writing.